DEVELOPMENT OF POTENTIAL RELIGIOUS TOURISM OBJECTS SYEKH BURHANUDDIN'S TOMB IN NAGARI MANGGOPOH PALAK GADANG ULAKAN ULAKAN TAPAKIS DISTRICT PADANG PARIAMAN DISTRICT - habib habiburrakhman habiburrakhman; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The purpose of this research is to find out: The aim of this research is to find out: 1) To find out the potential development of the religious tourism object Sheikh Burhanuddin's Tomb in Nagari Manggopoh Palak Gadang Ulakan, Ulakan Tapakis District, Padang Pariaman Regency. 2) Knowing the impact of developing the potential religious tourism attraction of Sheikh Burhanuddin's Tomb in Nagari Manggopoh Palak Gadang Ulakan, Ulakan Tapakis District, Padang Pariaman Regency. The method used in this research is Mix Methods, with an approach of associating qualitative and quantitative forms. The data used in the research is primary data, namely data originating from interviews and field observations, as well as SHP data for the research area. The analysis technique used is the SWOT method which is used to determine the potential for developing religious tourism at the Sheikh Burhanuddin Tomb in Nagari Manggopoh Palak Gadang Ulakan, Ulakan Tapakis District, Padang Pariaman Regency. This research shows that Sheikh Burhanuddin's Tomb has the potential to be a religious tourist attraction and cultural heritage with worship facilities, religious values ​​and strategic location. Based on the four aspects analyzed, it was found that two aspects have a feasibility interpretation value in the very good category, namely based on IFAS and EFAS, Sheikh Burhanuddin's Tomb has great potential to be developed as a religious tourist attraction and cultural heritage. Meanwhile, the impact of developing the religious tourism potential of Sheikh Burhanuddin's Tomb on the community's economy is increasing community income, creating new economic areas and increasing local business in tourist attraction areas as well as positive social and environmental impacts on the community.